Translating habitat class to land cover to map area of habitat of terrestrial vertebrates - Maria Lumbierres; Prabhat Raj Dahal; Moreno Di Marco; Stuart H. M. Butchart; Paul F. Donald; Carlo Rondinini (Conservation Biology, 2022)
Area of habitat (AOH) is defined as the “habitat available to a species, that is, habitat within its range” and is calculated by subtracting areas of unsuitable land cover and elevation from the range. The International Union for the Conservation of Nature (IUCN) Habitats Classification Scheme provides information on species habitat associations, and typically unvalidated expert opinion is used to match habitat to land‐cover classes, which generates a source of uncertainty in AOH maps. We developed a data‐driven method to translate IUCN habitat classes to land cover based on point locality data for 6986 species of terrestrial mammals, birds, amphibians, and reptiles. We extracted the land‐cover class at each point locality and matched it to the IUCN habitat class or classes assigned to each species occurring there. Then, we modeled each land‐cover class as a function of IUCN habitat with (SSG, using) logistic regression models. The resulting odds ratios were used to assess the strength of the association between each habitat and land‐cover class. We then compared the performance of our data‐driven model with those from a published translation table based on expert knowledge. We calculated the association between habitat classes and land‐cover classes as a continuous variable, but to map AOH as binary presence or absence, it was necessary to apply a threshold of association. This threshold can be chosen by the user according to the required balance between omission and commission errors. Some habitats (e.g., forest and desert) were assigned to land‐cover classes with more confidence than others (e.g., wetlands and artificial). The data‐driven translation model and expert knowledge performed equally well, but the model provided greater standardization, objectivity, and repeatability. Furthermore, our approach allowed greater flexibility in the use of the results and uncertainty to be quantified. Our model can be modified for regional examinations and different taxonomic groups.